(untitled) (Studia Prawnicze / The Legal Studies, 2007)
Zmiany ustroju politycznego oraz modelu gospodarczego, które miały miejsce w Polsce po 1989 r., zmodyfikowały struktury administracji rządowej. Z organizacji administracji gospodarczej znikły organy resortowo-branżowe, a w ich miejsce pojawiły się organy regulujące oraz agencje, które wspomagają niedomogi niedostatecznie jeszcze wykształconych mechanizmów gospodarki rynkowej. Niniejszy artykuł ma na celu określenie prawnoadministracyjnej istoty regulacji jako nowej funkcji współczesnej administracji publicznej oraz pokazanie pozycji ustrojowej organów regulacyjnych w strukturze administracji publicznej. Punktem wyjścia do przedstawienia poszczególnych układów regulacyjnych występujących na tzw. rynkach regulowanych będzie analiza pojęcia regulacji. Postawione więc zostanie pytanie o przyczyny, a tym samym i cel wprowadzenia regulacji do gospodarki. Realizacja tego celu (lub celów) wiązać się będzie z koniecznością działania administracji publicznej na określonych obszarach. Działania organów regulacyjnych wyjaśniane będą przy zastosowaniu zarówno metody opisu obszarów ich działania, jak i opisu i analizy form działania. The subject of the study was defining legał and administrative aspect of regulation as the new function of contemporary public administration and the structural position of the regulatory bodies in the structure of the Polish public administration. The starting point to present particular regulatory systems existing on the so called regulated markets (i.e. raił transport market, fuel and energy market as well as telecommunication and post market) was the analysis of the term regulation. There was the ąuestion of the reasons for and aim of introducing the regulations to the economy. It is necessary that public administration is active on specified areas so that the aim (or aims) is met. Actions of the regulatory bodies were explained by using both the method of describing their areas of activity and the description and analysis of action forms. Difficulties to specify the content of the regulatory function unambiguously were the reason why the usage of research instrument in the form of legał control system to specify legał relations between regulatory body and participants of particular market as well as between bodies regulating particular market was suggested. The legał relations as a whole were defined as regulatory control system. In the summary I presented the conclusion saying that regulation is the new function of the contemporary public administration in Poland.